AB1137 Use of Complementary and Alternative Medicine is Associated with Increased Delay to Initiation of Disease Modifying Anti-Rheumatic Drug Therapy in Patients with Inflammatory Polyarthritis: Results from the Singapore Early Arthritis Cohort. (9th June 2015) - Lahiri, M.; Santosa, A.; Teoh, L.K.; Teng, G.G.; Cheung, P.
Abstract : Background: The use of complementary and alternative medicine (CAM) is common in some societies among patients with chronic diseases such as inflammatory polyarthritis (IP). The use of CAM may increase delay to rheumatologist assessment and initiation of disease modifying anti-rheumatic drug (DMARD) therapy. Objectives: To examine the use of CAM in a multi-ethnic, Asian inception cohort of patients with early IP and to determine its association with time to initiation of first DMARD (TIFD). Methods: We prospectively recruited all adult patients with IP arthritis affecting ≥2 peripheral joints and symptom onset after September 1, 2012 from the only two hospitals serving Western Singapore. Baseline data on demographics, CAM use, education level, language spoken, smoking, time of symptom onset and DMARD prescription, disease activity score in 28 joints (DAS28) and physical function (modified Health Assessment Questionnaire, mHAQ) were collected by face to face interview, chart review and assessment by a trained nurse. Predictors of CAM use were determined by multivariate logistic regression. The association of CAM use and TIFD (≤12 weeks, 12-24 weeks, >24 weeks) was determined by ordinal logistic regression. Missing values (<2%) were ignored. Results are presented as odds ratios (OR) and 95% confidence intervals (CI). Results: Of the 130 included patients (median (IQR) age 51.3 (41, 59.9) years, 71.5% women), 112 (86%) had physician-diagnosed rheumatoid arthritis. 61.5% were Chinese, 18.5% Malay and 13.1% were Indian. Median (IQR) disease duration from diagnosis was 3.6 (0, 20.7) weeks and median (IQR) delay from symptom onset to first rheumatologist review was 16.1 (9, 24.7) weeks. Patients had moderately active disease, with median (IQR) DAS28 at baseline of 4.1 (2.6, 5.4), but low functional disability with median (IQR) mHAQ score of 0.25 (0, 0.75). Fifty-three (41.4%) of 128 patients with available data admitted to either former or current use of CAM. Oral tablets or powder (55.1% of CAM users) and acupuncture (46.9%) were the most common types of CAM. In univariate logistic regression, Chinese race, being non-English speaking, smoking and high disease activity were significantly associated with CAM use. In a multivariate model, Chinese race, being non-English speaking, smoking and additionally education level were independent predictors of CAM use (Figure ). TIFD was increased in CAM users (median 20.6 weeks vs. 15.3 weeks in non-users, p=0.01, Wilcoxon-Mann-Whitney). In multivariable analysis adjusted for age, gender, race, DAS28 and mHAQ, CAM use (along with mHAQ) was an independent predictor of TIFD. CAM use was significantly associated with increased TIFD (OR 2.77 vs. non-users, 95% CI 1.24-6.19, p=0.01) while the converse was seen with mHAQ (OR 0.2 for mHAQ ≥1 vs. <1, 95% CI 0.07-0.6). Conclusions: CAM use is common, especially in older, non-English speaking Chinese smokers with high disease activity and may lead to a delay in presentation and initiation of DMARD therapy. Healthcare professionals should be aware of these unique challenges in treating patients with early arthritis in Asia. Acknowledgements: The Chapter of Rheumatologists, College of Physicians, Academy of Medicine, Singapore. Disclosure of Interest: None declared